Mechanization Status, its Technical Indicators and Impact on the Wheat Crop Production in Iraq (Agricultural Engineering, 2023)
Increase of the number of tractors and harvesters working in agriculture improves significantly the number of agricultural land operations, harvest efficiency and eliminates primitive farming methods. The production expansion is either horizontal through exploitation and reclamation of more areas or vertical such as introduction of technological variables in the same unit area. The current study aims to investigate the gap of the ratio of the number of tractors and harvesters to the agricultural area, its technical indicators and its impact on the wheat crop production. Data were obtained from agricultural departments and divisions of the Salah al-Din Agriculture Directorate to calculate some of the indicators of the technological and technical evaluation. Tables were prepared with the numbers of tractors and agricultural harvesters that cover the cultivation and harvest campaign. Their horsepower was proven and then converted to the kilowatt unit, as well as the agricultural areas within the agricultural plan that is implemented by the Directorate for four seasons. The surplus power of agricultural tractors contributed to the increase in the executed agricultural areas and requirements of agricultural operations such as tillage, harrows, and leveling contrary to agricultural harvesters, in which case there was a gap in the decrease of the number of agricultural combines in relation to the implemented agricultural plan, which, as a result, may cause a loss in wheat crop harvesting on the specified date. The mechanical harvest contributed to the increase in the grain received from the wheat by the grain trading company in the province, which brings economic returns to the farmer.